Facile synthesis, characterization, molecular and dynamic optical properties of metronidazole and sulfamethoxazole adducts of tricarbonyl(1-5-η-2-methoxycyclohexadienylium)iron - Tunmise Tunrayo Eugene-Osoikhia; Adewale Saheed Olawoyin; Torhile Japhet Aasegh; Nnenna Winifred Odozi; Nathanael Damilare Ojo; Temidayo Oyetunde; Emmanuel Oloruntoba Yeye; Raymond Akong Akong; Emmanuel Usman Onche; Oluwatoba Emmanuel Oyeneyin; Ibrahim Adebayo Oladosu (Discover Chemistry)
Abstract Research on energy materials, especially those with optical applications is trending. Here, we synthesized new tricarbonyl [1,4-η-5-(4-amino-N-(5-methyl-1,2-oxazol-3yl)benzenesulfonamide) cyclohexa-1,3-diene]iron (1SF) and tricarbonyl[1,4-η-5-(2-(2-methyl-5-nitroimidazol-1-yl)ethanol)cyclohexa-1,3-diene] iron (1MF) by the modification of sulfamethoxazole (1S) and metronidazole (1 M) via their nucleophilic addition to 2-methoxydienyliumiron cation ([(1-5-η-2-MeOC6H6)Fe(CO)3] [PF6]. Demetallation of 1SF and 1MF resulted in the modified forms of metronidazole (1MD) and sulfamethoxazole (1SD). The synthesized 1,3-diene iron tricarbonyl derivatives were characterized using infrared and Nuclear Magnetic Resonance (1H NMR and 13C NMR) spectroscopic methods. The molecular and nonlinear optical (NLO) properties of the ligands (1S, 1 M), adducts (1SF, 1MF) and demetallated forms (1SD, 1MD) were investigated using density functional theoretical approach for a good understanding of the optical processes. The electronic absorption of the materials was in the ultraviolet region except 1MF with absorption edge at 490 nm. The static [β(0;0,0); γ(0;0,0,0): ħω = 0] and dynamic NLO properties (electrooptic Pockels’ effect [EOPE: β(-ω;ω,0)], electrooptic Kerr’s effect [EOKE: γ(-ω;ω,0,0)], second harmonic generation [SHG: β(-2ω;ω,ω)], direct current second harmonic generation [DCSHG: γ(-2ω;ω,ω,0)]) computed at ħω = 0.0428 au laser frequency were compared with those of urea (standard). The molecular softness, chemical reactivity and kinetic instability of the compounds increased in the order 1S < 1SF < 1SD < 1 M < 1MF < 1MD as observed from the energy gap (3.01–5.27 eV). The dynamic NLO properties were greater than those of urea. The β(0;0,0) and β(-ω;ω,0) were 8–14 times greater than urea, while the EOKE and DCSHG were 3–14, and 3–196 times higher, respectively. The 1MF and 1MD displayed greater NLO properties than 1 M. Also, 1SF exhibited higher EOPE, EOKE, SHG and DCSHG than 1S and 1SD, suggesting the potential application of the materials in optical communications, optical switches and optical data storage devices.